Digitalization of Societies: The Strengths and Weaknesses of the Dynamics of the Digital Information Age and the Information Society - Muhalani, Raisul; Dhini, Hafizah Rahma (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Several adagiums proposed by observers of the development of modern communication suggest that information has become one of the vital elements in society. Information becomes a fundamental need to be described as an impulse vein that supports political, social, and business decision-making. As a result, societies must be exposed to the growth and dynamics of new media as well as global communication. The faster cycles of information production, consumption, and distribution are experienced and owned by a new global society system supported by the strength and expansion of the economy, the networking of global information systems, and the contribution of digital technology. This research method uses a library study. This article will present alternative discourses to look at the advantages and weaknesses of the information technology processes that ultimately bring society into the digital age.